Florida Solid and Hazardous Waste Regulation Handbook: Emergency Planning and Community Right-to-Know Act (EPCRA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
The Emergency Planning and Community Right-to-Know Act (EPCRA) was passed in 1986 to improve emergency response to accidental releases of toxic and/or hazardous chemicals into the environment. EPCRA primarily serves a planning purpose. It required governors to set up State Emergency Response Commissions (SERCs). Those commissions then set up Local Emergency Planning Committees (LEPCs). This is EDIS document FE448, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.